HGG-36. NFκB AND FOXM1 MEDIATE ANTI-CANCER ACTIVITY OF DUAL HDAC AND PI3K INHIBITION IN PEDIATRIC HIGH GRADE GLIOMA AND DIPG. Issue 2 (22nd June 2018) - Pal, Sharmistha; Kozono, David; Yang, Xiaodong; Fitts, Whitney; Ni, Jing; Alberta, John; Zhao, Jean; Liu, Kevin; Bian, Jie; Truffaux, Nathalene; Weiss, William; Resnick, Adam; et al.
Abstract: Pediatric high-grade gliomas (pHGGs) and diffuse intrinsic pontine gliomas (DIPGs), portend a poor prognosis and are particularly recalcitrant to standard treatment. Aberrant chromatin remodeling and activation of the phosphatidylinositol 3-kinase (PI3K) pathway have been identified as important mediators of pHGG and DIPG pathogenesis. As inhibition of these pathways are promising therapeutic avenues and radiation is the only modality to prolong survival of DIPG patients, we sought to explore radiosensitizing functions of such inhibition and explore mechanisms of action of such agents. Here, we demonstrate that treatment with CUDC-907, a novel, first-in-class dual inhibitor of histone deacetylases (HDACs) and PI3K, in combination with radiotherapy evokes a synergistic cytotoxic response in pHGG and DIPG models in vitro and in vivo. We identify a novel mechanism of CUDC-907 in modulating DNA damage response by inhibiting radiation-induced DNA repair pathways, including homologous recombination and non-homologous end joining. The radiosensitizing effects of CUDC-907 were mediated by decreasing NFκB/Forkhead box M1 (FOXM1) recruitment to promoters of genes involved in the DNA damage response, and exogenous expression of NFκB/FOXM1 rescued CUDC-907-induced cytotoxicity. Together, these findings reveal CUDC-907 as a novel radiosensitizer with potent anti-tumor activity in pHGG and DIPG, and provide a preclinical rationale for the combination of CUDC-907 with radiotherapy as a novel therapeutic strategy for pHGG and DIPG. More globally, we have identified NFκB and FOXM1, and their downstream transcriptional elements, as critical targets for new treatments for pHGG and DIPG.